2022
DOI: 10.3390/atmos13050716
|View full text |Cite
|
Sign up to set email alerts
|

Detailed Carbon Isotope Study of PM2.5 Aerosols at Urban Background, Suburban Background and Regional Background Sites in Hungary

Abstract: The aim of this study was to estimate and refine the potential sources of carbon in the atmospheric PM2.5 fraction aerosol at three sampling sites in Hungary. Quantification of total, organic and elemental carbon (TC, OC and EC, respectively), as well as radiocarbon (14C) and stable carbon isotope analyses were performed on exposed filters collected at an urban background site, a suburban background site of the capital of Hungary, Budapest from October 2017 to July 2018. Results were also collected from the ru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 53 publications
0
0
1
Order By: Relevance
“…Note also from Table 3 that a very high contribution of modern carbon f c , likely associated with a larger biomass burning contribution, was observed only in 2 samples (W1 and W6). The values of f c reported in this study resulted slightly higher than those found by Major et al (2022) who analyzed PM2.5 samples in different urban background, suburban background, and rural sites in Budapest (Hungary). In more detail, they found seasonal mean f c values between 50 and 78% suggesting that modern sources were significant during the observation year, regardless of the heating or vegetation periods.…”
Section: Samplecontrasting
confidence: 88%
“…Note also from Table 3 that a very high contribution of modern carbon f c , likely associated with a larger biomass burning contribution, was observed only in 2 samples (W1 and W6). The values of f c reported in this study resulted slightly higher than those found by Major et al (2022) who analyzed PM2.5 samples in different urban background, suburban background, and rural sites in Budapest (Hungary). In more detail, they found seasonal mean f c values between 50 and 78% suggesting that modern sources were significant during the observation year, regardless of the heating or vegetation periods.…”
Section: Samplecontrasting
confidence: 88%